2016
DOI: 10.1007/s00262-015-1781-6
|View full text |Cite
|
Sign up to set email alerts
|

A randomized phase II clinical trial of personalized peptide vaccination with metronomic low-dose cyclophosphamide in patients with metastatic castration-resistant prostate cancer

Abstract: This study investigated the effect of metronomic cyclophosphamide (CPA) in combination with personalized peptide vaccination (PPV) on regulatory T cells (Treg) and myeloid-derived suppressor cells (MDSC), and whether it could improve the antitumor effect of PPV. Seventy patients with metastatic castration-resistant prostate cancer were randomly assigned (1:1) to receive PPV plus oral low-dose CPA (50 mg/day), or PPV alone. PPV treatment used a maximum of four peptides chosen from 31 pooled peptides according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 35 publications
0
57
1
Order By: Relevance
“…All patients provided written informed consent for study participation and data collection. The results of all 5 clinical trials were reported previously . In the present study, the data of these trials were used to analyze the peptides that correlated with clinical benefits.…”
Section: Methodsmentioning
confidence: 96%
“…All patients provided written informed consent for study participation and data collection. The results of all 5 clinical trials were reported previously . In the present study, the data of these trials were used to analyze the peptides that correlated with clinical benefits.…”
Section: Methodsmentioning
confidence: 96%
“…At least two positive responses were also required on the pretreatment peptide‐specific IgG titer test for HLA matched peptides in 31 candidate peptides. Safety and immunological effects of the 31 candidate peptides were previously reported . All patients were required to be 20 years of age or older, have a performance status of 0 or 1 in accordance with EOCG, have a life expectancy of 12 weeks or more, an HLA haplotype of HLA‐A2, ‐A24, ‐A26, ‐A3, ‐A11, ‐A31, or ‐A33, and no hepatic or renal dysfunction.…”
Section: Methodsmentioning
confidence: 99%
“…Personalized peptide vaccination (PPV) is also gaining ground, based on the concept of boosting preexisting host immunity. In the most recent randomized phase II clinical trial, PPV combined with metronomic lowdose cyclophosphamide in patients with metastatic castrateresistant prostate cancer prolonged OS of those patients who responded immunologically after vaccination, i.e., mounted peptide-specific humoral and CTL responses (59).…”
Section: Peptide Vaccines Can Generate Effective Anti-tumor T Cell Rementioning
confidence: 99%